2017
DOI: 10.1017/s0033291717003403
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical changes in people with high schizotypy: relationship to glutamate levels

Abstract: Our study shows that GMV findings in schizotypy are related to glutamate levels, supporting the hypothesis that glutamatergic function may lead to structural changes associated with the expression of psychotic-like experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 62 publications
(90 reference statements)
2
31
0
Order By: Relevance
“…Thus, the observed group differences in hippocampal CBF in the present study are unlikely to be confounded by underlying GMV effects from this region. Noteworthy, our recent multimodal structural imaging study in this same sample did not find hippocampal volume differences between the groups (Modinos et al, 2017a), consistent with all other neuroanatomical investigations in schizotypy (DeRosse et al, 2015;Ettinger et al, 2012;Kuhn, Schubert, & Gallinat, 2012;Modinos et al, 2010;Nenadic et al, 2015;Wang et al, 2015;Wiebels, Waldie, Roberts, & Park, 2016).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, the observed group differences in hippocampal CBF in the present study are unlikely to be confounded by underlying GMV effects from this region. Noteworthy, our recent multimodal structural imaging study in this same sample did not find hippocampal volume differences between the groups (Modinos et al, 2017a), consistent with all other neuroanatomical investigations in schizotypy (DeRosse et al, 2015;Ettinger et al, 2012;Kuhn, Schubert, & Gallinat, 2012;Modinos et al, 2010;Nenadic et al, 2015;Wang et al, 2015;Wiebels, Waldie, Roberts, & Park, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…There are some limitations to this study. First, subjects were recruited from a university sample, had relatively high IQs and groups showed no differences in self-reported substance use; therefore, our Third, our sample was relatively small, and recruitment through selfreport has previously been related to higher rates in schizotypy scores (Linscott & van Os, 2010 (Modinos et al, 2017a), following the proposal that GMV could represent a potential confounder in ASL studies (Asllani, Borogovac, & Brown, 2008;Chappell et al, 2011). This analysis yielded no significant effects within or between groups either at p < .05 FWE or at a more lenient threshold of p < .001 uncorrected.…”
Section: Discussionmentioning
confidence: 99%
“…In several previous studies, primarily variations in precuneus structure and function have, repeatedly, been associated with schizotypal traits and subclinical PLEs (Modinos et al ., 2010, 2018; van Lutterveld et al ., 2014; Falkenberg et al ., 2015; Nenadic et al ., 2015b). It is, therefore, unexpected that we did not find any association with any of the SPQ dimensions in this region in our data.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is growing evidence for fronto-striatal circuits to be involved in the generation of PLEs. Recent studies have suggested positive schizotypal traits to be associated with variations in frontal volume, but the direction is unclear, with increases (Kühn et al ., 2012; Nenadic et al ., 2015b; Modinos et al ., 2018) as well as decreases (Ettinger et al ., 2012; DeRosse et al ., 2015) being reported. As most studies have focused on variations in volumetric parameters, apart from one study finding increased right prefrontal lobe gyrification in participants scoring above v. below a clinical cut-off (Stanfield et al ., 2008), there is no study using a dimensional approach to schizotypy and folding analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation